2013
DOI: 10.2174/1381612811319340007
|View full text |Cite
|
Sign up to set email alerts
|

Avocado (Persea americana) Seed as a Source of Bioactive Phytochemicals

Abstract: The pulp of avocado (Persea americana, Lauraceae) has been reported to have beneficial cardiovascular health effects. Avocado oil is used for dermatological applications and its unsaponifiable portion is reported to have beneficial effects against osteoarthritis. Although the seed represents a considerable percentage of the total fruit, scientific research on the phytochemistry and biological effects of avocado seeds is in the nascent stages,. Currently, the seed represents an under-utilized resource and a was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
0
21

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(121 citation statements)
references
References 0 publications
3
82
0
21
Order By: Relevance
“…Phenol has the highest percentage in aqueous extracts compared to ethanol and n-hexane extracts. High percentage of phenol is in agreement with the findings of Dabas et al [18] who reported that avocado are rich in phenol which plays a major role in body system of an individual. The presence of phenol in avocado fruit helps to reduce cardiovascular disease (CVD) risk by reducing oxidative and inflammatory stress [19].…”
Section: Resultssupporting
confidence: 92%
“…Phenol has the highest percentage in aqueous extracts compared to ethanol and n-hexane extracts. High percentage of phenol is in agreement with the findings of Dabas et al [18] who reported that avocado are rich in phenol which plays a major role in body system of an individual. The presence of phenol in avocado fruit helps to reduce cardiovascular disease (CVD) risk by reducing oxidative and inflammatory stress [19].…”
Section: Resultssupporting
confidence: 92%
“…In addition, the protective effects of dietary consuming avocado oil on biochemical markers of liver function in rats fed with sucrose were quite similar to olive oil [86]. Furthermore, a study has shown that avocado seeds improved hypercholesterolemia, and facilitated the prevention and treatment of hypertension, inflammatory conditions, and diabetes [87]. …”
Section: Experimental Studiesmentioning
confidence: 99%
“…[1] The avocado fruit, also known as the alligator pear or butter pear, is characterized by the presence of only one seed, which is encased in a hard shell and corresponds to 16% of the fruit weight. [2] Some studies have shown that avocado seeds can be used as raw material for oil and pigment production; [3] however, they are usually discarded in the environment as by-products.…”
Section: Introductionmentioning
confidence: 99%